Towards peculiar corrosion behavior of multi-main-phase Nd-Ce-Y-Fe-B permanent material with heterogeneous microstructure. (December 2020) - Peng, Baixing; Jin, Jiaying; Liu, Yongsheng; Lu, Chenxi; Li, Lingwei; Yan, Mi
Graphical abstract: For the first time, we present that the heterogeneous microstructure of Ce/Y/La-based multi-main-phase (MMP) magnets, the origin of intergrain and intragrain Volta potential discrepancy (a), initiates peculiar corrosion mechanisms: (b) preferential corrosion of RE-rich intergranular phase yields an abnormal increase in the corrosion resistance, which is ascribed to high surface integration of stable REFe2 and RE2 Fe14 B phases; (c) local Ce-rich region with lower Volta potential, including Ce-rich shell (type I, upper red rectangle) and Ce-rich core (type II, bottom blue rectangle), evolves as crucial proceeding source of pit corrosion within 2:14:1 grain. Highlights: Whole-process corrosion behavior of multi-main-phase magnet was firstly investigated. Heterogeneous microstructure is the origin of intergrain/intragrain potential discrepancy. Abnormally increased anti-corrosion is closely correlated to intergranular heterogeneity. Local Ce-rich shell/core with lower potential evolves as preferential sites for pit corrosion. Abstract: Heterogeneous microstructure of multi-main-phase (MMP) Nd-Ce-Y-Fe-B sintered magnet is unraveled to generate local electrode potential discrepancy of intergranular multi-phases and intragrain core-shells, being the origin of peculiar corrosion behaviors relative to conventional Nd-Fe-B. i) For intergranular heterogeneity, the preferential corrosion of active RE-rich phase yields an abnormal enhancement of anti-corrosion performance. ii) For intragrain heterogeneity, local Ce-rich shell and Ce-rich core with lower Volta potentials evolve as preferential sites for pit corrosion, resulting in large cavities and apparent Ce-oxide accumulation. Above findings unlock the close correlation between heterogeneous microstructure and whole-process corrosion behavior of MMP magnets for the first time.